Dis/Consent: Persepectives on Sexual Consent and Sexual Violence - Johannah May Black (Atlantis)
Book under review: Malinen, KelleyAnne, ed. 2019 Dis/Consent:Persepectives on Sexual Consent and Sexual Violence. Black Point: Fernwood Publishing.